PELATIHAN PENGURUSAN JENAZAH BAGI SISWA MADRASAH ALIYAH NEGERI (MAN) 3 JOMBANG - Makhisoh, Iis; Hasbullah, Abdur Ro'uf (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract Funeral and corpse management, or Tajhizul Janaiz, is one of the obligations that must be carried out by Muslims, both young and old. The phenomenon in society is that the management of moslem corpses is handed over to the elders, and it is rare for the younger generation to have the knowledge and skills. Therefore, this community service activity takes partners from the high school level. The method used is service learning with five stages: investigation, planning, implementation, reflection, and demonstration. The output of this service activity is in the form of: 1) knowledge regarding corpse management; 2) practical understanding of corpse management; 3) skills in handling corpses; and 4) preparation of partners as the younger generation who have responsibility for managing corpses. Training for high school students, apart from providing an active learning model whose methods are not only theoretical in class, also provides a sense of responsibility as part of society. Keywords: Tajhizul janaiz, Corpse management Training, Highschool   Abstrak Pemakaman dan pengurusan jenazah (Tajhizul Janaiz) merupakan salah satu kewajiban yang wajib dilaksanakan oleh umat Islam, baik tua maupun muda. Fenomena yang terjadi di masyarakat, pengelolaan jenazah umat Islam diserahkan kepada orang yang lebih tua, dan jarang sekali generasi muda yang memiliki pengetahuan dan keterampilan. Oleh karena itu, kegiatan pengabdian kepada masyarakat ini mengambil mitra dari tingkat Sekolah Menengah Atas (SMA). Metode yang digunakan adalah service learning dengan lima tahapan yaitu investigasi, perencanaan, pelaksanaan, refleksi, dan demonstrasi. Luaran kegiatan pengabdian ini berupa: 1) pengetahuan mengenai pengelolaan jenazah; 2) pemahaman praktis pengelolaan jenazah; 3) keterampilan penanganan jenazah; dan 4) penyiapan mitra sebagai generasi muda yang mempunyai tanggung jawab dalam pengelolaan jenazah. Pelatihan bagi siswa SMA selain memberikan model pembelajaran aktif yang metodenya tidak hanya teori di kelas, juga memberikan rasa tanggung jawab sebagai bagian dari masyarakat. Kata Kunci: Tajhizul janaiz, Pelatihan pengelolaan jenazah, SMA